From Happy Customers to Brand Advocates: The Power of Satisfaction - Alam, Syed Hasnain; Zaman, Sohaib Uz; Rajput, Asif Mehmood (Pakistan Journal of Humanities and Social Sciences, 2025)
The objective of this study is to examine the mediating role of customer satisfaction between product quality, brand image, and online shopping experience in influencing customer loyalty in e-commerce sector. Primary data was collected from 383 online consumers during the first quarter of 2024. A cross-sectional survey was conducted using a structured questionnaire. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to test the hypothesized direct and mediation effects. Results reveal that product quality and online shopping experience significantly influence customer satisfaction (? = 0.99 and ? = 0.92, respectively), while brand image has an indirect effect. Customer satisfaction, strongly predicts customer loyalty (? = 0.98), as strong predictor in mediation. The structural model predicts the overall 71.7% of the variance in Customer loyalty. This research integrates theoretical models of ECT, SERVQUAL, and ELM to highlight the dominant role of digital experience and satisfaction on product features in shaping e-loyalty behavior. The finding indicates that product quality and online shopping experience have great impact on consumer loyalty, while brand image does not influence consumer loyalty directly.